The effects of interset rest duration on muscle activation and performance during resistance training - Mohamad Shahrul Azzfar Mohamad Azzeme (Tanjong Malim, 2019)
The effects of interset rest duration on muscle activation and performance during resistance training by Mohamad Shahrul Azzfar Mohamad Azzeme